Insta Famous Syarif Hidayatullah dalam Memasarkan Produk Digital pada akun instagram @padukacapcut. - Mulya, Muhamad Alief Abbyan; Agustini, Vilya Dwi; Putra, Gilang Kumari (LPPM Universitas Jambi, 2025)
This study explores the role of Insta Famous Syarif Hidayatullah in promoting digital products through his Instagram account @padukacapcut. The research aims to understand how influencers can independently build, market, and monetize educational content using social media. Applying Pierre Lévy’s new media theory, this study views Instagram not only as a channel of communication but also as a participatory space that fosters social interaction and knowledge exchange. Using a descriptive qualitative method, data were collected through interviews, observation, and documentation. The findings indicate that Syarif utilizes a combination of organic strategies—such as educational Reels and Stories—and paid strategies through Instagram Ads. These are designed with soft-selling and hard-selling approaches tailored to different audience segments. He also emphasizes responsive communication by actively engaging with followers through comments and direct messages, which helps establish trust and drive conversion. The implication of this research highlights the transformation of influencers from mere promoters to self-driven entrepreneurs who can leverage digital platforms to create business ecosystems based on personal branding and user interaction. This study contributes to the discourse on influencer marketing and digital entrepreneurship in the context of new media environments.